2021
DOI: 10.1111/ijcp.14827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stroke cases with other neurological diseases on the basis of haemogram parameters

Abstract: Aims This study aimed to examine the haemogram parameters, including the neutrophil/lymphocyte ratio (NLR), which is fast, easy and practical to determine, in stroke patients who present with more physiological stress and inflammation and compare them with patients presenting other neurological diseases. Methods The demographic, laboratory and imaging features of all patients who were admitted to the neurology clinic within a three‐year period and met the study criteria were retrospectively analysed. A haemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Hemogram-based inflammatory parameters have been previously investigated in stroke patients. For example, a previous study found that high WBC and platelet values were associated with mortality [ 17 ]. The results of the current study have consistently shown that these hemogram-based parameters are much higher in cases of mortality than in survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemogram-based inflammatory parameters have been previously investigated in stroke patients. For example, a previous study found that high WBC and platelet values were associated with mortality [ 17 ]. The results of the current study have consistently shown that these hemogram-based parameters are much higher in cases of mortality than in survivors.…”
Section: Discussionmentioning
confidence: 99%
“…As per the findings of the present study, the CRP levels were also significantly higher in non-surviving stroke cases compared to survivors. Various prognostic ratios such as NLR, PLR, and CLR provide insights into the prognosis of critical illness as well as ischemic stroke cases [ 11 , 17 - 19 ]. In this study, NLR, PLR, and CLR were significantly different in the non-surviving cases.…”
Section: Discussionmentioning
confidence: 99%